Pilot Study of Nasal Expiratory Positive Airway Pressure Devices for the Treatment of Childhood Obstructive Sleep Apnea Syndrome - Kureshi, Suraiya A. (American Academy of Sleep Medicine, 2014)
STUDY OBJECTIVES: Alternative therapies for childhood obstructive sleep apnea syndrome (OSAS) are needed as OSAS may persist despite adenotonsillectomy, and continuous positive airway pressure (CPAP) adherence is low. Nasal expiratory positive airway pressure (NEPAP) devices have not been studied in children. We hypothesized that NEPAP would result in polysomnographic improvement. Further, we aimed to determine NEPAP adherence, effects on sleepiness, behavior, and quality of life. METHODS: A randomized, double-blind, placebo-controlled, crossover pilot study was performed. CPAP candidates, 8-16 years old, underwent NEPAP and placebo polysomnograms. Subjects with ≥ 50% reduction in the apnea hypopnea index (AHI) from placebo to NEPAP night or AHI < 5/h on NEPAP night wore NEPAP at home for 30 days. Adherence was assessed by daily phone calls/emails and collecting used devices. RESULTS: Fourteen subjects (age 13.4 ± 1.9 years, BMI z-scores 2.2 ± 1 [mean ± SD]) were studied. There was significant improvement in the obstructive apnea index with NEPAP vs. placebo: 0.6 (0-21.1)/h vs. 4.2 (0-41.9)/h (median [range], p = 0.010) and trends for improvement in other polysomnographic parameters. However, responses were variable, with 3 subjects not improving and 2 worsening. Older children and those with less hypercapnia had a better response. Eight subjects were sent home with devices; one was lost to follow-up, and adherence in the remainder was 83% of nights; these subjects had a significant improvement in sleepiness and quality of life. CONCLUSIONS: NEPAP devices are a potential alternative therapy for OSAS in a small subset of children. Due to variability in individual responses, efficacy of NEPAP should be evaluated with polysomnography. CLINICAL TRIAL REGISTRATION: www.clinicaltrials.gov, identifier: NCT01768065 CITATION: Kureshi SA, Gallagher PR, McDonough JM, Cornaglia MA, Maggs J, Samuel J, Traylor J, Marcus CL. Pilot study of nasal expiratory positive airway pressure devices for the treatment of childhood obstructive sleep apnea syndrome. J Clin Sleep Med 2014;10(6):663-669.